Indonesia's Foreign Policy Trajectory Under President Prabowo Subianto: Balancing Assertiveness and Pragmatism in an Evolving Global Order - Setiawan, Asep (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This article examines the potential trajectory of Indonesia's foreign policy under the leadership of President Prabowo Subianto. Drawing on Prabowo's past statements, actions as Defense Minister, and early moves as President, the analysis projects how Indonesia may navigate key regional and global challenges. The research finds that Prabowo is likely to pursue a more assertive and hands-on foreign policy approach compared to his predecessor, while still adhering to Indonesia's foundational "free and active" doctrine. Key areas of focus are expected to include strengthening Indonesia's position within ASEAN, carefully balancing relations with major powers like the US and China, boosting defense capabilities and diplomacy, and elevating Indonesia's role as an influential middle power. However, Indonesia will face constraints in fully realizing a more muscular foreign policy due to domestic priorities and limited hard power capabilities. Prabowo's foreign policy will likely blend nationalist rhetoric with pragmatic engagement, as Indonesia seeks to enhance its strategic autonomy and global influence amid shifting geopolitical dynamics.